Well-Being, Skills and Work in a Neorepublican EU: The Case of Third-Country Nationals - McCormack-George, Dáire Aaron (Trinity College Dublin. School of Law. Discipline of Law, 2020)
This is a work in special analytic jurisprudence and applied normative political theory. It applies neorepublican political theory to people at work in the EU, taking third-country nationals as a case study. Empirical data suggests that third-country nationals habitually experience inadequate skills recognition and wrongful discrimination when seeking access to and participation in the Single Market. Their well-being is consequently negatively affected. Accordingly, the central research question which this thesis investigates is the extent to which the EU guarantees the well-being of third-country nationals in accessing work in the EU, with a particular focus on skills recognition and freedom from discrimination as aspects of their well-being in accessing work. The answer to this question comes in two parts. Part I grounds the thesis in a value theoretic concern for people s well-being in accessing work, focussing on their freedom to work through the exercise of their skills as an aspect thereof. It then provides a partial exposition and application of neorepublicanism to people at work in the EU, defending the possibility of a neorepublican justification of EU labour law. More specifically, it justifies two rights of relevance to the lived experience of third-country nationals, namely, the rights to work and to non-discrimination. In the light of a theoretical commitment to neorepublicanism, Part I argues that third-country nationals should generally be entitled to equal treatment with member state nationals. Part II applies the theoretical framework developed in Part I to third-country nationals right to have their skills recognised when moving to and within the EU, a derivative right of the core right to work which is afforded to third-country nationals through treating them more or less equally with EU nationals. It critiques EU law and policy as it stands in the light of a neorepublican commitment to justice at work in the EU. It is suggested that EU law as it stands is deficient in numerous respects insofar as it fails to treat third-country nationals equally with EU nationals in respect of their right to have their skills recognised and related legal and policy entitlements, such as labour market integration measures and access to education and training. Some possible reforms are suggested to better cohere with the account of neorepublican justice at work in the EU advanced in Part I.
APPROVED
Keywords: Republicanism/neorepublicanism/non-domination; Skills; Third-Country Nationals; Recognition of Professional Qualifications; Equality and Anti-Discrimination Law; Labour Law; EU Law